Development of design capabilities in smaller companies in the automotive industry : a methodological approach - Santos, Ricardo Cameira dos (2019)
ABSTRACT: This paper reflects part of a broader investigation on the development of methodologies to identify, value and manage design capabilities in order to create a sustainable competitive advantage. With the automotive industry and smaller supplier Portuguese companies as background, this paper explores the resource-based view theory (RBV) and the dynamic capabilities theory as a theoretical construct for a further development of research tools. In the automotive industry, OEM (Original Equipment Manufacturers) continue to control the overall design of the vehicle, as part of the ability to manage the offer portfolio and brand communication. However, the industry have been moving towards an increasing participation of smaller suppliers in product development processes, pushed towards capabilities’ development as a requirement to continue competitive in the OEM’s suppliers network. The role of design and design management capabilities have been explored as strategic resources or core competencies. However, Design is not typically found in smaller supplier firms as resource (as opposed to Design studios in larger companies) but found as a process in resourcecapability combinations, establishing the need for a new research approach. Therefore, the RBV is a tool to value the design process as a sustained competitive advantage. The RBV conceptualizes a framework to determine or identify the strategic resources available or needed within a company. At these lenses, the basis for a sustainable competitive advantage lies in the application of the bundle of valuable resources identified and at the firm's disposal and the combinations with its capabilities